COVID-19 VACCINATION AND DENTISTRY: ARE WE FACING NEW CHALLENGES OR WORKING WITHIN OUR POSSIBILITIES? ANALYTICAL REVIEW - Myroslav Goncharuk; Renata Pohorilyak; Mariia Stetsyk; Alessandro Leite Cavalcanti; Yasemin Yavuz; Maryana Pasichnyk (Cumhuriyet University, 2022)
Objective. To systematize available data regarding COVID-19 vaccination aspects among dental specialists and highlight relevant occupationally-related features of vaccination challenges. Materials and Methods. Search of pertinent literature sources associated with above-formulated objective was provided via PubMed Central database (https://www.ncbi.nlm.nih.gov/) and Google Scholar search engine (https://scholar.google.com/). Criteria of publication date included 2020-2021 years period. Publications in English or at least with English abstract/summary were collected within primary sample for further preliminary content-analysis. All articles collected for in-depth content-analysis were evaluated due to the text-mining, text-identification and text-extraction principles with further clusterization and systematization of outcomes at the Microsoft Excel 2019 software (Microsoft Office, 2019). Results. After full reading of articles' texts 24 of them were interpreted as those containing new and/or unique information, interpretations or facts, out of which 9 were cross-sectional online surveys, 4 were editorials, 6 were literature/clinical reviews, 1 was brief report, 1 was opinion article, 1 was ethical moment, 1 was advice article, and 1 was web-source. New challenges related with COVID-19 vaccination within dental filed are represented by personal hesitancy of dental professionals and students, which in turn associated with provided information support, previous COVID-19 experience, fear of getting infected or transmit disease to the patients or family members, fear of potential development for post-vaccination side-effects, changes of occupational status, and interaction within dental team. Conclusions. Further improvement of dental care field possible only after vaccination of dental professionals. Vaccination of dentists widening window of their possibilities regarding potential role of dental specialist as members of COVID-19 vaccine's delivery team, improvement of quality of life among dental patients (after its decreasing changes during pandemic), and providing dentists with important role in so-called "behaviorally informed strategies" and public motivational programs aimed at amplification of positive willingness for COVID-19 vaccination among general public.